The PELATIHAN DAN PEMBANGUNAN ANIMASI CONSTRUCT BERBASIS WEB DENGAN TEMATIK LINGKUNGAN SEKITAR DI TK ARROHMAH KARANGJUWET: TRAINING AND PROGRAM ANIMATION GAME EDUCATION THEMATIC ARROUND NEIGHBORHOOD AT TK AR ROHMAH KARANGJUWET MALANG - Ariadi Retno Tri Hayati Ririd (LPPM Universitas Abdurrab, 2025)
Training for teachers in TK Ar Rohmah Karangjuwet Malang have some purpose in introducing animation game for children for education teaching, introducing how to play the application game education that built for TK Ar Rohmah Karangjuwet. Animation in game in this training for knowledge about application already build by our team with curriculum about surrounding environmental at school TK Ar Rohmah Karangjuwet in Malang. Animation in this training is displayed animation for objects in indoor or outdoor and child character try to find correct objects for get points in game application. This application including education for children and try to make help children more easy in learn about curriculum sub theme around environment. Animation in this training is built with Contruct in web based with design of objects use Inkscape application by team. In this application game there are two level, first about indoor lesson and next level for outdoor lesson as secondly level in animation game application. In this application has character as equipped for interactive game animation as child character where find objects in each level and the result is get point influenced with time and correct answer in finished animation game education point and can be access in web.